Differences Netizen Responses on Social Media X and Instagram About Post Indonesian Demonstrations: A Sociolinguistics Study - Nurul Apriani Ymaniyar; Nurul Na'imahtul Rahma; Maharani Laksmi Anindita (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This research aims to explicitly describe the language used by netizens on social media platforms X and Instagram in posts about demonstrations in Indonesia, and to identify and analyze the social factors influencing these language choices. The primary objective is to compare netizen responses—specifically focusing on their linguistic characteristics—on X and Instagram, and to assess how social media platform characteristics and user objectives contribute to these differences. The research method used is documentation with data analysis techniques. The data and sources used in this study are comments on demonstrations in Indonesia that include specific words or phrases. The results of this study indicate differences in the language used by netizens on social media X and Instagram, including: 1) language use on social media X tends to be highly sarcastic and sharp, using swear words, profanity, and even expletives; 2) language use on Instagram shows two polarizations, namely indirect and direct language use; and 3) there are social factors that influence the differences in netizen responses, such as differences in social media characteristics, netizen objectives, and the presence of social media as a forum for freedom of expression. This study specifically for research on language use in virtual spaces as it reflects the diverse and complex expressions of social media users, particularly regarding linguistic phenomena in society and contributes to sociolinguistic research.